Circuit Models to Study the Radiated and Conducted Susceptibilities of Multiconductor Shielded Cables Connected to Non-linear Load - Mohamed Saih; Zahra Bouzidi; Youssef Rhazi (Majlesi Journal of Electrical Engineering)
This paper presents an efficient Multiconductor Shielded Cable model, for conducted and radiated coupling, developed for circuit applications. In the case of radiated coupling, the interaction of the external incident field is modeled by equivalent voltage and current generators placed on shield only. The model works in frequency and time domain with linear and non-linear loads, respectively. Different applications are presented, for validation and physical interpretation. Finally, we will discuss the effect of the connection of the voltage limiter on the induced voltages.